FEATURES OF THE COURSE AND TREATMENT OF GLOMERULONEPHRITIS IN CHILDREN - Batirovna, Ibragimova Yulduz (PT. Antis International Publisher, 2025)
Objective: Glomerulonephritis in children represents a significant medical condition characterized by acute or chronic inflammation of the renal glomeruli, stemming from an infectious-allergic etiology. Understanding its clinical manifestations and establishing precise diagnostic and therapeutic approaches are vital for effective management. Methods: Diagnosis of glomerulonephritis in children involves a combination of medical history analysis, evaluation of clinical symptoms, laboratory testing, ultrasound imaging, and kidney puncture biopsy. Treatment in the acute phase integrates bed rest, a regulated diet, and pharmacological interventions, including antibiotics, corticosteroids, anticoagulants, diuretics, hypotensive agents, and immunosuppressive drugs. Results: The acute form is identified by a triad of symptoms: urinary syndrome (oliguria, anuria, hematuria, proteinuria), edema, and hypertension. Chronic forms may exhibit the predominance of one syndrome or present a latent course. Timely diagnosis and appropriate treatment improve the prognosis, reduce complications, and support recovery. Novelty: This study highlights the critical role of a multifaceted diagnostic approach combining clinical, laboratory, and imaging techniques. Additionally, it underscores the comprehensive pharmacological management strategies tailored to the acute and chronic manifestations of glomerulonephritis in children.